Relationship between Tourism Expansion and Telecommunication in Thailand - NONTHAPOT, Sakkarin; WATCHALAANUN, Tanawat (Journal of Environmental Management and Tourism, 2016)
Telecommunications remains a major infrastructure problem in Thailand where international tourist numbers are gradually increasing. This paper examines the causal relationship between the number of international tourist arrivals and telecommunication investment in Thailand. Using annual data from 1983-2013, the results confirm that the number of international tourist arrivals and telecommunication investment are cointegrated and stable. The causality analysis reveals that there is bi-directional causality between the two variables in the long-run. This study suggests policymakers should upgrade the telecommunication service provided in the country and recognizing the investment in the telecommunications industry, they should focus on international tourism promotion by directly communicating efficiently to enhance and maintain the target group for international tourist arrivals. Additionally, Thailand's government should find a policy to induce investors for investment in telecommunications which supports tourism supply development. This will lead to augmenting the tourism market in Thailand.
Keywords: tourism; tourism development; telecommunication; Rolling Window Bound testing